ANALISIS STRATEGI PENGEMBANGAN BISNIS JASA ETALASE DALAM PERSPEKTIF EKONOMI ISLAM PADA TOKO SEMOGA JAYA GROUP DI KECAMATAN IV NAGARI KABUPATEN SIJUNJUNG - Yelvi Andriani; Novera Martilova (CV. Adiba Aisha Amira, 2023)
The purpose of this study was to find out and analyze how the SWOT analysis of the storefront service business in the Harapan Jaya Group in IV Nagari District, Sijunjung Regency and to find out and analyze the business development strategy analysis for storefront services in a sharia perspective in the hopefully jaya group store in IV Nagari District, District Sijjung. Based on the results of research conducted using SWOT analysis, the strategy used is the S-O (Strengths-Opportunities) strategy with a score of 4.35, using opportunities to minimize existing opportunities, namely: maintaining product quality and adjusting product quality to market demands so that customers have more confidence and loyal to the products provided by the May Jaya Group store, and always prioritizes the wishes of customers so that customers are satisfied with what the May Jaya Group store provides. The business development strategies implemented by the Selamat Jaya Group store are: innovating, choosing the right location, improving product quality, and prioritizing customer service. Of these strategies, there is a strategy that has the most influence on the May Jaya Group Store, namely the strategy to improve product quality. From the business development strategy carried out by the Harapan Jaya Group, there are obstacles in running its business, namely: Promoting a product and a lack of human resources.